Innovation for agricultural climate risk insurance: household survey preliminary report - Muriithi, Cyrus K; Osiemo, Jamleck; Mwongera, Caroline (2022)
This document reports on preliminary findings from a household survey conducted in Meru County under the auspices of the Innovation for African Climate Risk Insurance (INACRI). The project aims to develop an improved crop insurance index that addresses basis risk inter alia for small scale maize farmers. The goal of the household survey was to assess farmer’s production risks, crop insurance needs and willingness to adopt crop insurance. We also assess farmer’s financial and insurance literacy as a robustness check for their preferences for insurance. In addition, we highlight some key demographic characteristics of the farmers such as education, age, farm size, and main occupation. We find that agriculture is the primary source of income for over 68% of the farmers, over 51% have attained at least a primary school education, and about 24% are withing the age bracket of 36 – 45 years. Findings on risk perceptions indicate that drought, and pests and diseases are the most frequently mentioned sources of uncertainty in production. While most studies report that farmers are averse to risk, the farmers we interviewed portray a relatively low aversion to risk when we consider small financial stakes (aversion to risk might vary depending on the domain of the risk). Regarding demand for insurance, farmers tend to have a high willingness to accept maize crop insurance. However, we highlight that this finding should be evaluated further because many factors not considered in our analysis could result in a false positive on the demand. We also find that farmers prefer multiple peril insurance to single peril insurance. Though preference for multiple peril insurance is in line with rational choice in a context of many risk sources, multiple peril insurance can be relatively expensive. Regarding insurable interests, we find that yield is the most preferred. This finding is plausible because yield insurance may cover several other perils. Finally, we find that farmers tend to have a high preference for insurance bundled with fertilizer, improved seeds and agricultural advisories, and the use of digital (mobile) platforms in the payment of premiums and requesting compensation.